Immunogenicity of Intranasally Administered Meningococcal Native Outer Membrane Vesicles in Mice - Saunders, Nancy B. (American Society for Microbiology, 1999)
Colonization of the human nasopharyngeal region by Neisseria meningitidis is believed to lead to natural immunity. Although the presence of bactericidal antibody in serum has been correlated with immunity to meningococcal disease, mucosal immunity at the portal of entry may also play an important role. This study was undertaken to examine in mice the possibility of safely using native outer membrane vesicles (NOMV) not exposed to detergent as an intranasal (i.n.) vaccine. The mucosal and systemic responses of mice to intranasal and intraperitoneal (i.p.) vaccination with NOMV were compared over a range of doses from 0.1 to 20 μg. Intranasal vaccination of mice with NOMV induced a strong systemic bactericidal antibody response, as well as a strong local immunoglobulin A immune response in the lung as determined by assay of lung lavage fluid by enzyme-linked immunosorbent assay and lung antibody secreting cells by enzyme-linked immunospot assay. However, 8- to 10-fold-higher doses of NOMV were required i.n. compared to i.p. to elicit an equivalent bactericidal antibody response in serum. Some NOMV vaccine was aspirated into the lungs of mice during i.n. immunization and resulted in an acute inflammatory response that peaked at 1 to 2 days postimmunization and was cleared by day 7. These results indicate that i.n. delivery of meningococcal NOMV in mice is highly effective in eliciting the production of both a mucosal immune response and a systemic bactericidal antibody response.